Evaluasi Kinerja Embung Kecil di Kabupaten Ende - Melani, Maria Agustina Henny; Udiana, I Made; Sina, Dantje Arie Tresna (JUTEKS : Jurnal Teknik Sipil, 2024)
There are 23 small dams in Ende Regency that have experienced decline in function which affects the purpose of building the reservoir, namely to fulfill the needs of household clean water, crops, and livestock. The research aims to evaluate the performance of small dams in Ende Regency based on four aspects, physical aspects, utilization aspects, operational and maintenance (O&M) aspects and organizational management aspects. The performance of the reservoirs in terms of physical aspects using the Observation and Documentation Method, utilization aspects, O & M aspects and organizational management aspects using the Questionnaire Method. The results obtained the percentage of small reservoir performance in terms of physical aspects with unfavorable reservoir conditions amounted to 62.62%. The percentage of utilization aspects is 53.60%. The percentage value of the O & M aspect of 55.40% is not good. The percentage of organizational management aspects is 51.83% in poor condition. From the four aspects reviewed, it was found that the performance of small dams in Ende Regency had decreased founction by 62,62%. The solution to overcome the decline in the function of the small dams is the rehabilitation of the components of the dam, improvement of road access and subsidies and the establishment of a water user organization to coordinate all activities related to harvesting